"Japan's foreign aids policy to Africa" : the cases of Angola and Mozambique within the TICAD process - Carvalho, Pedro Miguel Raposo de Medeiros, 1969- (2020)
This article presents an overview of the authors' doctorate thesis. It investigates about Japanese foreign aid to Africa during and after the Cold War and in relation to the process that has emerged in the before and after the Tokyo International Conference on Africa Development (henceforth TICAD) Process. Specifically, it examines an empirical case study of the TICAD as an intersection of international relations theory and decision-making policy mostly of Japanese Ministry of Foreign Affairs (MOFA) in order to address Japanese aid to Africa particularly to Angola and Mozambique from a long-term perspective. The author argues that the TICAD Process is a clear case of efforts by Japan and particularly MOFA to achieve Japanese national interests. To this end, TICAD links several policies such as peacekeeping and aid combined with trade and investment. A major conclusion is that the Japanese aid priority areas towards Angola and Mozambique are consistent with the TICAD after the Cold War and with Japan's attempts to replicate its Asian development experiences to Africa, as well as with human security objectives as a component of Japanese foreign policy and guiding principle of Japan's ODA in the XXI century. Finally, the article is divided in three broad parts: introduction, development and main findings and conclusion.